Biomechanical report for the IAAF World Indoor Championships 2018 triple jump women - Tucker, C.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The women`s triple jump took place on the morning of Saturday 3rd March. This was a thrilling final during which the medal positions were keenly contested and personal bests were produced by three of the top four athletes. At the halfway point the lead was held by Kimberly Williams of Jamaica with a third round effort and personal best of 14.48 metres. Spain`s Ana Peleterio produced a personal best of 14.40 metres with her fourth round jump which placed her in the bronze medal position. However, it was the current outdoor world champion, Yulimar Rojas of Venezuela, who produced a jump that would not be beaten in the fifth round. Her effort of 14.63 metres - a world leading jump - was enough to clinch the gold medal.